Weak and strong convergence theorems for a countable family of strict pseudocontractions in Banach spaces - Prasit Cholamjiak (2018)
We first investigate the weak convergence of the Mann-type iterative scheme for a countable family of strict pseudocontractions in a uniformly smooth Banach space which is uniformly convex or satisfies Opial's condition. Then the strong convergence theorems of the modified Mann-type iterative scheme are also proved in a uniformly smooth Banach space. As a consequence, several weak and strong convergence theorems for an infinite family of pseudocontractions are established. © 2013 Taylor & Francis.